Green Glyphosate Treatment with Ferrihydrite and CaO2 via Forming Surface Ternary Complex - Zhang, Nuanqin; Sun, Hongwei; Zhan, Guangming; Zu, Junning; Zhang, Lizhi (Environmental science & technology, 2025)
Glyphosate (PMG) is a globally used broad-spectrum herbicide and receives environmental concerns because of its moderate persistence and potential carcinogenicity. Traditional PMG treatment methods often suffer from the generation of a more toxic and persistent aminomethylphosphonic acid (AMPA) intermediate. Herein, we develop a green method with ferrihydrite (FH) and CaO2 (FH/CaO2) via regulating the coordination of PMG with FH and Ca2+, where the phosphonate group of PMG preferentially binds to FH and its carboxylate side complexes with Ca2+ released by CaO2, forming a FH-PMG-Ca ternary surface complex. This unique ternary complex can redistribute electrons within the PMG molecule for its C–P activation and C–N bond stabilization, favoring the selective C–P bond attack of superoxide radical produced by the Fenton reaction between CaO2-derived H2O2 and FH, thus generating environment-friendly glycine instead of AMPA. The FH/CaO2 process realizes over 99% PMG degradation in industrial wastewater within 1 h, with residual PMG < 0.1 ppm and AMPA < 40 ppb. More importantly, the CaO2 consumption was as low as 3.1 mg of CaO2/mg of PMG, one-fifth those of previously reported CaO2-based counterparts. This study provides an effective and environment-friendly PMG treatment strategy and highlights the importance of surface coordination modes on the degradation pathway of PMG.